2020
DOI: 10.15835/nbha48111777
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticle and pyridoxine seed priming improves tolerance to salinity in milk thistle seedling

Abstract: Application of growth regulators plays important role under salt conditions. Perspectives to overcome these limitations by chitosan nanoparticle (CSNP: 0, 0.25, 0.5, and 1%) and pyridoxine (PN: 0, 0.03, 0.06, and 0.09%) seed priming was studied in both experiments with milk thistle seeds exposed to NaCl as salt stress (0, 50, 100, and 150 mM). Salinity threshold and EC50 (the salinity level that 50% of germination reduction) achieved 74.85 and 213.5 mM, respectively. A significant reduction in germination perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Soil salinity is one of the main problems in arid and semiarid areas that affect the growth and productivity by interfering with the nutritional status of plants through complex interaction mechanisms. The typical salt challenged plants to exhibit reduced nutrient absorption, poor transport of nutrients from roots to shoots, decreased dry leaf and stunted root growth, degradation of leaf pigments like chlorophyll and carotenoids affecting photosynthetic machinery, and causing a reduction in overall growth (Ashour, Esmail, & Kotb, 2020;Mosavikia, Mosavi, Seghatoleslami, & Baradaran, 2020;Safikhan, Khoshbakht, Chaichi, Amini, & Motesharezadeh, 2018;Sen, Chouhan, Das, Ghosh, & Mandal, 2020;Zayed, Elkafafi, Zedan, & Dawoud, 2017). Reactive oxygen species (ROS) are reactive molecules that cause oxidative stress, damage to proteins and nucleic acids, produce excess malondialdehyde (MDA) by inactivating antioxidant enzymes and ultimately causes cell death under salt stress (Sheikhalipour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil salinity is one of the main problems in arid and semiarid areas that affect the growth and productivity by interfering with the nutritional status of plants through complex interaction mechanisms. The typical salt challenged plants to exhibit reduced nutrient absorption, poor transport of nutrients from roots to shoots, decreased dry leaf and stunted root growth, degradation of leaf pigments like chlorophyll and carotenoids affecting photosynthetic machinery, and causing a reduction in overall growth (Ashour, Esmail, & Kotb, 2020;Mosavikia, Mosavi, Seghatoleslami, & Baradaran, 2020;Safikhan, Khoshbakht, Chaichi, Amini, & Motesharezadeh, 2018;Sen, Chouhan, Das, Ghosh, & Mandal, 2020;Zayed, Elkafafi, Zedan, & Dawoud, 2017). Reactive oxygen species (ROS) are reactive molecules that cause oxidative stress, damage to proteins and nucleic acids, produce excess malondialdehyde (MDA) by inactivating antioxidant enzymes and ultimately causes cell death under salt stress (Sheikhalipour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various applications of Cs-NPs have been found to increase salinity tolerance in plants (Sen et al, 2020;Sheikhalipour et al, 2021;Zayed et al, 2017). It is even more interesting to see the composition of CsBMs in mitigating the deleterious effect of salt stress on bitter melon (Sheikhalipour et al, 2021), maize (Oliveira et al, 2016), milk thistle (Mosavikia et al, 2020), and periwinkle (Hassan et al, 2021). Despite using CsBMs alone to improve the productivity and quality of several crops, the use of modified CsBMs gained more advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Mosavikia et al (2020) concluded that limited stomatal conductance, diminished activities of carbon fixation enzymes, reduced quantities of photosynthetic pigments, and destruction of photosynthetic apparatus are among the key factors limiting the process of photosynthesis under salinity stress conditions.…”
Section: Correlation Coefficientsmentioning
confidence: 99%
“…Enzymatic and non-enzymatic antioxidants response are defensive mechanisms to overcome oxidative stress (Demidchik, 2015). Proline and sugar, non-enzymatic antioxidants response, are known to act as an osmolyte/osmoprotectant agent under drought or salinity stress (Mosavikia et al, 2020). The osmolyte has an important role in scavenging free radicals, osmotic pressure adjustment, stabilizing sub-cellular structures, and storing carbon and nitrogen (Gorzi et al, 2017).…”
Section: Correlation Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation